A multicultural comparative study of self‐stigma in epilepsy: Differences across four cultures - Takayuki Iwayama; Kimihito Mizuno; Esra Yildiz; Kheng‐Seang Lim; Soon Ming Yi; Yee Joe Lynn; Ching Woon Hin; Jason Chia Zhi Jean; Si‐Lei Fong; Yu Xuen; Ong Zhi Qian; Izumi Kuramochi (Epilepsia Open)
Abstract Objective Epilepsy is a neurological disorder characterized by recurrent seizures, exhibiting variance in prevalence and treatment availability across diverse geopolitical contexts and cultural milieus. The stigma associated with epilepsy is a significant global issue affecting the quality of life (QOL) of people with epilepsy (PWE). This study aims to examine the relationship between self‐stigma and depressive symptoms in PWE, with a particular emphasis on understanding the manifestations of these across different cultural contexts. We aim to enhance the provision of customized care to diverse cultural settings, fostering the adoption of healthier lifestyles for PWE. Methods We recruited PWE who received treatment at specialized medical facilities for epilepsy in Japan, Malaysia (Chinese, Malay), and Turkey from February to October 2023. The Epilepsy Self‐Stigma Scales (ESSS), Neurological Disorders Depression Inventory for Epilepsy (NDDI‐E), and Generalized Anxiety Disorder 7 (GAD‐7) in local languages were used to assess self‐stigma, depressive symptoms, and anxiety. Results The ESSS total scores were significantly higher among the Turkish and Japanese cohorts (F [3, 406] = 6.57, p < 0.001, η2 = 0.05). In addition, the self‐stigma observed moderate positive correlations for depressive symptoms (rs = 0.41–0.50, Ps < 0.001) and anxiety (rs = 0.42–0.44, Ps < 0.001). The ANCOVA findings suggested that the notable variations in self‐stigma, as found in the one‐way ANOVA conducted across four cultures, were reduced when taking into consideration depressed symptoms. Our finding highlights the potential influence of mental health factors over cultural factors concerning self‐stigma. Significance The manifestation of self‐stigmatization within epilepsy exhibits distinctions across diverse cultural cohorts, regardless of the demographic and clinical variation, yet demonstrates a significant correlation with psychological factors. In subsequent research endeavors, we should comprehensively investigate these subtle differences, their potential impact on patient care, and the development of supportive approaches. Plain Language Summary This cross‐cultural study reveals significant variations in self‐stigma among people with epilepsy across different cultural contexts, with Turkish and Japanese cohorts showing higher levels. Self‐stigma demonstrated moderate positive correlations with depressive symptoms and anxiety across all cultures. Notably, differences in self‐stigma were reduced when accounting for depressive symptoms, suggesting that mental health factors may have a stronger influence than cultural factors. These findings underscore the importance of considering both cultural and psychological aspects in developing targeted interventions to address self‐stigma in epilepsy care.